Modeling the land use and pedestrian environment for the rail-based transit-oriented development towards realizing NKRA initiatives for an improved urban public transportation system - Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor; Jaafar Sidek, Mohd Farid; Nik Othman, Nik Nurul Aziemah; Bakri, Fatahsha Amira (International Islamic University Malaysia, 2018)
The main focus of this research is to evaluate the effects of land use density, land use diversity, pedestrian infrastructures on rail-based transit ridership. From the previous literature, it is well known that these three main components would have adverse effects on transit ridership – the higher the land use density, diversity, and good pedestrian infrastructures, the higher the increase in transit ridership. Some of the main findings from the analysis on the effects of 3Ds (density, diversity, design) on passenger ridership show a mixed result. Generally, the findings concur with previous literature in which the transit stations having high land use density and diversity were patronizing high passenger ridership and similarly lower passenger rideship at transit stations with low land use density and diversity. Nevertheless, it was also found out that some other transit stations along the selected LRT line having high land use density and diversity were found to be patronizing low passenger ridership. Similarly, some other transit stations having low land use density and diversity were found to be patronizing high passenger ridership. The likely reasons for high land use density and diversity but low passenger ridership are inappropriate location of transit stations, and absence of feeder bus services from the neighboring residential areas to the transit station. On the other hand, the likely reasons for low land use density and diversity but high passenger ridership are presence of park and ride facilities at the transit station and regular provision of feeder bus services. The correlation analysis that was applied to all the selected variables shows some of the variables were highly correlated but some other variables were weakly correlated. The variables such as the “existence of interchange to other modes of transport”, “interchange to ERL”, “bicycle rack availability”, “residential, and open spaces” are correlated with average daily ridership for Kelana Jaya line LRT stations. The variables such as “interchange to other modes of transport”, “connecting station”, “residential and institutional” land use are correlated with average daily ridership for Ampang line LRT stations. The variables such as “interchange to other modes of public transport”, “interchange to ERL”, “residential and commercial” land use were correlated with average daily ridership for both lines (Kelana Jaya and Ampang) when combined; The key findings from linear regression model show “interchange to other modes of public transport”, “interchange to ERL” and “commercial development surrounding rail stations” can able to increase rail transit ridership. The findings from this study are expected to contribute towards realizing the public policies in improving the use of public transport in major cities in Malaysia. The alignment of future transit line especially the transit station should be planned and located at places where the surrounding development is at least medium land use density and diversity. Additionally, the provision of well-connected pedestrian infrastructures connecting the transit station to the surrounding land use also increases rail transit ridership. To complement the increase in the use of public transit, other main station infrastructure such as park and ride facilities, feeder bus services must also be considered when planning transit stations.